Real Convergence Across the Euro Area - Leonor Coutinho; Alessandro Turrini (Intereconomics)
Abstract This paper studies the relationship between real convergence in the euro area and macroeconomic imbalances. It compares the main features of convergence within the euro area with other EU and non-EU country groups, looking at both ‘sigma’ and ‘beta’ convergence in output and total factor productivity. Expected convergence paths for euro area countries are estimated using growth regressions run on a large panel of advanced and emerging market economies and compared to actual growth. The findings support the view that EU and euro area countries display similar convergence patterns to those of other country groups, while the group of countries that adopted the euro first exhibit relatively weak convergence since before the financial crisis. Such differences could be partly linked to relatively low dispersion in per capita incomes across this country group, although lack of convergence is also largely due to persisting differences in total factor productivity performance. The findings also suggest that macroeconomic imbalances accumulated in the pre-crisis period such as high private and government debt and strong growth in the non-tradable sector have been associated with lower convergence, particularly for euro area countries.